The effect of transport on live weight loss, meat quality and blood haematology in slaughter ostriches - Wolmarans, Wilhelm J. (Stellenbosch : University of Stellenbosch, 2011)
Thesis (MScAgric (Animal Sciences))--University of Stellenbosch, 2011.